Space charge limited current and photoconductive effect in few-layer MoS2. (May 2019) - Grillo, A; Giubileo, F; Iemmo, L; Luongo, G; Urban, F; Di Bartolomeo, A
Abstract: We analyse the conduction mechanism and the electrical photoresponse of chemical-vapor deposited MoS2 few-layers on SiO2 /Si substrate. We perform temperature dependent I-V measurements and report a space-charge limited conduction due to the presence of an exponential distribution of trap states in the MoS2 band-gap. We estimate the density of trap states as 10 10 – 10 11 cm −2 from the temperature-independent critical drain-source voltage. We also investigate the MoS2 photocurrent under white light at different incident powers. We use a modified Hornbeck-Hayens model to study the photoconductive effect and for an alternative estimation of the trap state density.